OPTIMALISASI KINERJA GURU PADA PENDIDIKAN DASAR: STRATEGI PENGELOLAAN GURU UNTUK PENINGKATAN HASIL BELAJAR SISWA - Suparno; Marheni Rayung Puspaningrum (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the challenge of optimizing teacher performance to improve student learning outcomes in elementary schools. Despite the critical role of teachers in shaping student achievement, many schools face issues related to limited pedagogical competence, insufficient use of varied teaching methods, and low motivation among teachers. The study aimed to identify the factors affecting teacher performance and develop strategies for effective teacher management. A qualitative descriptive approach with a case study design was employed, involving semi-structured interviews with teachers and school principals, classroom observations, and document analysis of lesson plans, supervision reports, and student assessment results. Findings indicate that teacher pedagogical competence, implementation of interactive and contextual teaching methods, motivation, effective classroom management, and support from academic supervision and school leadership are key factors influencing teacher performance. Teachers who apply interactive strategies and utilize digital media enhance student engagement and learning outcomes, while those relying on conventional lecture methods create passive classrooms, resulting in lower motivation and achievement. The study highlights that optimizing teacher performance requires an integrated approach combining professional development, supervision, motivation, and classroom management. These findings provide practical implications for school leaders and policymakers in designing programs to improve teaching quality and student competence in elementary education.